2009
DOI: 10.1007/s10661-009-1107-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring health implications of pesticide exposure in factory workers in Pakistan

Abstract: The study aimed to determine the hazardous health effects of pesticides exposure in the factory workers by measuring plasma cholinesterase (PChE), pesticides residues, and renal and hepatic biochemical markers. In addition, we also assessed the knowledge, attitudes, and safety practices adopted by the industrial workers. The study was conducted in three different sizes of factories located in Lahore (large), Multan (medium), and Karachi (small) in Pakistan. Total 238 adult males consisting of 184 pesticide ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 31 publications
4
36
0
7
Order By: Relevance
“…It has been reported that the pyrethroid metabolite concentration in human urine ranges from 0.318 to 189 ppb [37][41] and that the CYP residue in human serum can be as high as 0.3 ppm [42]. We chose to use a CYP concentration of 1×10 −7 −1×10 −5 M (0.42–42 ppb) in the medium.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the pyrethroid metabolite concentration in human urine ranges from 0.318 to 189 ppb [37][41] and that the CYP residue in human serum can be as high as 0.3 ppm [42]. We chose to use a CYP concentration of 1×10 −7 −1×10 −5 M (0.42–42 ppb) in the medium.…”
Section: Methodsmentioning
confidence: 99%
“…The raise of serum biochemical markers, which suggest liver dysfunction, or at least impairment of normal liver function, in those occupationally engaged to farming, has been previously reported [29,30,35], either by simultaneous alterations of all biomarkers [36], or via slight increases of certain components [34]. Total proteins levels were slightly higher among farmers in the present study, while other studies found no difference [35] or even lower total proteins levels in farmers [29,31] as a reflection of liver dysfunction. The increase in C-reactive protein (CRP) levels is an indicator of non-specific inflammation and oxidative stress in farmers’ population.…”
Section: Discussionmentioning
confidence: 97%
“…Unsafe practices can lead to measureable health effects in workers exposed to pesticides [17]. Interview surveys of agricultural workers in Thailand linked unsafe pesticide practices such as failing to use personal protective equipment (PPE) and using a higher than recommended concentration of pesticide to decreased serum cholinesterase activity, a marker of OP and carbamate pesticide exposure [12,18].…”
Section: Introductionmentioning
confidence: 99%